Pengaruh Asimetri Informasi, Alokasi Sumber Daya, Etika dan Komitmen Organisasi terhadap Budget Slack: Suatu Eksperimen - Ernita, Etti (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2007)
This study is investigated the effects of information asymmetry, resources allocation, ethics and organizational commitment on budget slack. Subjects consist of 73 undergraduate accounting at University of Sanata Dharma Yogyakarta. This study uses a 3x2 factorial design. This experiment manipulates information asymmetry into three conditions: low, middle, high information asymmetry and resources allocation into two conditions: no-resources allocation condition and resources allocation condition. This study predicts that budget slack is different between three of condition asymmetry information asymmetry, condition of resources alocation, ethics and organizational commitment. Subordinate with low ethics and organizational commitment tend to create higher slack than subordinate with high ethics and organizational commitment. Result show that there are different budget slack between low ethics and high ethics, and between low organizational commitment and high organizational commitment. Future research is make resources alocation treatment more perfect.